A Homeodomain-Containing Transcriptional Factor PoHtf1 Regulated the Development and Cellulase Expression in Penicillium oxalicum - Guo, Hao; Xu, Gen; Wu, Ruimei; Li, Zhigang; Yan, Mengdi; Jia, Zhilei; Li, Zhonghai; Chen, Mei; Bao, Xiaoming; Qu, Yinbo (Frontiers in Microbiology, 2021)
Homeodomain-containing transcription factors (Htfs) play important roles in animals, fungi, and plants during some developmental processes. Here, a homeodomain-containing transcription factor PoHtf1 was functionally characterized in the cellulase-producing fungi Penicillium oxalicum 114-2. PoHtf1 was shown to participate in colony growth and conidiation through regulating the expression of its downstream transcription factor BrlA, the key regulator of conidiation in P. oxalicum 114-2. Additionally, PoHtf1 inhibited the expression of the major cellulase genes by coordinated regulation of cellulolytic regulators CreA, AmyR, ClrB, and XlnR. Furthermore, transcriptome analysis showed that PoHtf1 participated in the secondary metabolism including the pathway synthesizing conidial yellow pigment. These data show that PoHtf1 mediates the complex transcriptional-regulatory network cascade between developmental processes and cellulolytic gene expression in P. oxalicum 114-2. Our results should assist the development of strategies for the metabolic engineering of mutants for applications in the enzymatic hydrolysis for biochemical production.